Ekstraksi dan Karakterisasi Nano Selulosa dari Limbah Kulit Bawang Merah - Angelina Nur Afni (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
Nanocellulose is a new type of material that is charavterized by an increase in cristalinity, surface area, increased dispersion, and biodegradation. One of ingredient that has not widely used and can be used as a source of nano cellulose, which is red onion skin. Red onion skin is part of the plant as a source of natural cellulose. The purpose of this research is to find out the extraction of nano cellulose from the red onion skin and characteristics of nano cellulose from the red onion skin. The research methods include lignin delignification steps, sample extraction, sample preparation, and characterization tests with XRD and SEM analysis techniques. The results obtained in the form nano cellulose powder with crystal size of 12,615 nm and morphology of nano cellulose from red onion skin which appear to be beum all fibers cellulose is defibrillated to fibrils because some cellulose fibers are still united to form bundle. The conclusion obtained is the synthesis of nano cellulose from the red onion skin done by delignification of cellulose from red onion skin, cellulose extraction, and characterization tests with XRD and SEM analysis techniques. Delignification produces red onion skin without blackish brown lignin, cellulose exraction will produce yellowish residue which will then be hydrolyzed and characterized using XRD and SEM analysis techniques.